The utilisation of child support grant by caregivers : the case of Ba-Phalaborwa sub-district in the Limpopo Province of South Africa. - Khosa, Priscalia (My University, 2013)
Children are part of the vulnerable population and mostly affected by poverty. The main policy response to children living in poverty in South Africa is the Child Support Grant (CSG). It is payable to a needy primary caregiver of a child for the benefit of that child. The aim of the CSG is to alleviate poverty among children. Although the grant is meant to benefit children, some of the caregivers misuse the grant resulting in children living in poverty. The study explored how caregivers in Ba-Phalaborwa sub-district in Limpopo Province utilise the CSG in the best interest of children. The researcher was motivated to conduct the study due to the reported cases of misuse of the CSG. It came to the researcher s attention that many caregivers do not utilise CSG in the best interest of children. Instead, caregivers use the grant for their own needs, leaving children s needs unmet. The study adopted a qualitative approach and it was exploratory in nature. The sample of the study was drawn from a population of 27 945 recipients of the CSG in the sub-district. A non-purposive sampling technique was used to select a sample of 20 caregivers aged between 21 and 50 who were also the beneficiaries of poor relief. A semi-structured interview schedule was used to collect data. The researcher conducted face-to-face individual interviews with 20 CSG recipients in Ba-Phalaborwa. The researcher also observed the participants home circumstances which further assisted her in data analysis. Thematic content analysis was used in analysing the data. The findings revealed that the CSG is mostly utilised to buy food, clothes and school necessities for children. This is a reflection that the grant does benefit children directly. Indirectly, the children benefit through contribution to burial societies with the grant. However, the findings further revealed that, there were perceptions that some recipients did not utilise the grant in the best interest of children. The misuse was through gambling and purchasing alcohol with grant. This disadvantages children. Suggestions were proposed on how those who misuse the grant can be dealt with. The suggestions included; initiating food vouchers, changing the recipient, monitoring, and punishing those who misuse the grant. In addition to the money being utilised to purchase food, clothes and school necessities for children, the findings also revealed that the participants were of the view that a slight amount of the grant need to be saved on a monthly basis so that it will help the children in future, especially when they go to tertiary institutions. However, participants complained about the inadequacy of the grant. VI Based on the research findings, it was recommended that if it is found that the recipients misuse the grant, someone should be appointed to receive the grant on behalf of the child and to use it for the benefit of that child. This should be done in collaboration with social workers and SASSA officials. Social workers should monitor the utilisation of CSG in order to ensure that the grant benefits children. Given the fact that the caseload for social workers is high, hiring other personnel (e.g. Auxiliary Social Workers) to deal specifically with the monitoring of the grant was recommended. The Auxiliary Social Workers can also assist families who are unable to manage their finances in drawing budgets with the CSG. It was further recommended that there is a need for South Africa to develop a comprehensive system of social protection which will enable caregivers to receive support in their own right. This would serve to ensure that the CSG is used specifically to meet the needs of children.
Keywords: Children; Child Support Grant; Caregivers; Social assistance; Social security; Poverty